Does tadalafil increase brain blood flow? The PASTIS trial. (20th December 2022) - Hainsworth, Atticus H; Pauls, Mathilde; Binnie, Lauren; Benjamin, Philip; Betteridge, Shai; Clarke, Brian; Dhillon, Mohani‐Preet; Ghatala, Rita; Hainsworth, Fearghal; Howe, Franklyn; Khan, Usman; Kruuse, Christina; et al.
Abstract: Background: This trial tested the hypothesis that the PDE5 inhibitor tadalafil, a widely‐used vasodilator, increases cerebral blood flow (CBF) in older people with symptomatic small vessel disease, the main cause of vascular cognitive impairment. Method: In a double‐blinded, placebo‐controlled, cross‐over trial, female and male participants received tadalafil (20mg) and placebo on two visits at least 7 days apart (randomized to order of treatment). The primary endpoint was change in subcortical CBF, with secondary outcome measures including change in cortical CBF and a panel of neuropsychological assays of cognition. The Perfusion by Arterial Spin Labelling Following Single Dose Tadalafil in Small Vessel Disease (PASTIS) trial was funded by the ADDF and the UK Alzheimer's Society (Clinical trial registration: clinicaltrials.gov/ct2/show/NCT02450253; eudract.ema.europa.eu/2015‐001235‐20). Result: Tadalafil increased CBF non‐significantly in all subcortical areas (N = 55, age: 66.8 (8.6) years) with greatest treatment effect within white matter hyperintensities (+9.8%, P = 0.0960). There were incidental treatment effects on systolic and diastolic blood pressure (‐7.8, ‐4.9 mmHg respectively; P<0.001). No serious adverse events were observed. Conclusion: The PASTIS trial did not identify a significant treatment effect of single‐administration tadalafil on subcortical CBF. To detect treatment effects may require different dosing regimens.